Special considerations for studies of extracellular vesicles from parasitic helminths: A community‐led roadmap to increase rigour and reproducibility. Issue 1 (5th January 2023) - White, Ruby; Sotillo, Javier; Ancarola, María Eugenia; Borup, Anne; Boysen, Anders Toftegaard; Brindley, Paul J.; Buzás, Edit I.; Cavallero, Serena; Chaiyadet, Sujittra; Chalmers, Iain W.; Cucher, Marcela A.; Dagenais, Maude; et al.
Abstract: Over the last decade, research interest in defining how extracellular vesicles (EVs) shape cross‐species communication has grown rapidly. Parasitic helminths, worm species found in the phyla Nematoda and Platyhelminthes, are well‐recognised manipulators of host immune function and physiology. Emerging evidence supports a role for helminth‐derived EVs in these processes and highlights EVs as an important participant in cross‐phylum communication. While the mammalian EV field is guided by a community‐agreed framework for studying EVs derived from model organisms or cell systems [e.g., Minimal Information for Studies of Extracellular Vesicles (MISEV)], the helminth community requires a supplementary set of principles due to the additional challenges that accompany working with such divergent organisms. These challenges include, but are not limited to, generating sufficient quantities of EVs for descriptive or functional studies, defining pan‐helminth EV markers, genetically modifying these organisms, and identifying rigorous methodologies for in vitro and in vivo studies. Here, we outline best practices for those investigating the biology of helminth‐derived EVs to complement the MISEV guidelines. We summarise community‐agreed standards for studying EVs derived from this broad set of non‐model organisms, raise awareness of issues associated with helminth EVs and provide future perspectives for how progress in the field will be achieved.